2007
DOI: 10.1103/physrevc.75.057901
|View full text |Cite
|
Sign up to set email alerts
|

System size effects and momentum correlations in heavy-ion collisions

Abstract: We aim to carry out the detailed study of system-size effects and momentum correlations by simulating the reactions of 12 C+ 12 C, Au at an incident energy of 400 MeV/nucleon and over entire colliding geometry from a central to an extreme peripheral one. A mass-independent role of the momentum correlations is reported for the entire periodic table. When averaged over all fragments, the effect of momentum correlations for central collisions is about 39%. All mass yields can be parametrized by a power law with 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In literature, several experimental as well as theoretical attempts have been made to explore the effect of incident beam energy, collision geometry and mass of the reacting partners on the fragmentation pattern [1][2][3][4]. In recent studies, Puri and co-workers found rise and fall of the multiplicity of intermediate mass fragments (IMFs) in accordance with experimental observations [5,6].…”
Section: Introductionmentioning
confidence: 67%
“…In literature, several experimental as well as theoretical attempts have been made to explore the effect of incident beam energy, collision geometry and mass of the reacting partners on the fragmentation pattern [1][2][3][4]. In recent studies, Puri and co-workers found rise and fall of the multiplicity of intermediate mass fragments (IMFs) in accordance with experimental observations [5,6].…”
Section: Introductionmentioning
confidence: 67%
“…However, in recent times many effective and proficient, algorithms are also available in the literature. The quantum molecular dynamics(QMD) generated phase space analysed through one such algorithm simulated annealing clusterization algorithm (SACA) [29] tends to solve the long standing problem of QMD method. The reactions are followed until the elliptical flow saturates i.e.…”
Section: Resultsmentioning
confidence: 99%